2014
DOI: 10.1094/mpmi-09-13-0267-r
|View full text |Cite
|
Sign up to set email alerts
|

Melanin Is Not Required for Turgor Generation but Enhances Cell-Wall Rigidity in Appressoria of the Corn Pathogen Colletotrichum graminicola

Abstract: The ascomycete and causative agent of maize anthracnose and stem rot, Colletotrichum graminicola, differentiates melanized infection cells called appressoria that are indispensable for breaching the plant cell wall. High concentrations of osmolytes accumulate within the appressorium, and the internal turgor pressure of up to 5.4 MPa provides sufficient force to penetrate the leaf epidermis directly. In order to assess the function of melanin in C. graminicola appressoria, we identified and characterized the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 66 publications
1
64
0
1
Order By: Relevance
“…In total, these studies have led to a better understanding of the early defense signaling mechanisms during pathogen infection and proliferation. For example, Ludwig et al [48] reported melanin as indispensable for pathogenesis in C . graminicola .…”
Section: Introductionmentioning
confidence: 99%
“…In total, these studies have led to a better understanding of the early defense signaling mechanisms during pathogen infection and proliferation. For example, Ludwig et al [48] reported melanin as indispensable for pathogenesis in C . graminicola .…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that osmolytes barrier was not provided by melanin in C. graminicola, may be same way it does in M. oryzae but melanin plays crucial role in rupture of cell wall (Ludwig et al, 2014).…”
Section: Effect Of Temperature On Appressoria Formation and Rate Of Amentioning
confidence: 81%
“…Recent experiment on Colletotrichum graminicola has shown that if melanin biosynthesis was inhibited than also pathogen could able to the penetration in leaves Meanwhile cell collapse assays showed that melanin was not required for turgour pressure in C. graminicola (Ludwig et al, 2014). This indicated that osmolytes barrier was not provided by melanin in C. graminicola, may be same way it does in M. oryzae but melanin plays crucial role in rupture of cell wall (Ludwig et al, 2014).…”
Section: Effect Of Temperature On Appressoria Formation and Rate Of Amentioning
confidence: 98%
“…According to Vittal et al (2014), the early events of uredospore germination, appressorium formation, and penetration of P. pachyrhizi on the soybean leaf occurred by 24 hai. The formation of appressoria is a pivotal event that allows a number of fungi to penetrate the leaf cuticle and establish a successful infection in their hosts (Chang et al, 2014;Dean, 1997;Loehrer et al, 2014;Ludwig et al, 2014;Mendgen and Deising, 1993). Certain biotrophic and hemibiotrophic fungi, such as those causing powdery mildews and anthracnose, respectively, can directly penetrate the cuticle through the action of cutinases, but in most cases, the strong osmotic pressure exerted by the melanized or not appressoria becomes detrimental (Dean, 1997;Ludwig et al, 2014;Mendgen and Deising, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The formation of appressoria is a pivotal event that allows a number of fungi to penetrate the leaf cuticle and establish a successful infection in their hosts (Chang et al, 2014;Dean, 1997;Loehrer et al, 2014;Ludwig et al, 2014;Mendgen and Deising, 1993). Certain biotrophic and hemibiotrophic fungi, such as those causing powdery mildews and anthracnose, respectively, can directly penetrate the cuticle through the action of cutinases, but in most cases, the strong osmotic pressure exerted by the melanized or not appressoria becomes detrimental (Dean, 1997;Ludwig et al, 2014;Mendgen and Deising, 1993). Other biotrophic fungi such as those causing rust can penetrate their host indirectly by entering the leaf mesophyll through stomata (Dean, 1997;Mendgen and Deising, 1993).…”
Section: Resultsmentioning
confidence: 99%